Vocal cord dysfunction in athletes: clinical presentation and review of the Llterature - Al-Alwan, A.; Kaminsky, D. (The Physician and Sportsmedicine, 2012)
Vocal cord dysfunction (VCD) is a syndrome characterized by the intermittent, abnormal paradoxical adduction of the true vocal cords during respiration resulting in variable upper airway obstruction. It is also commonly referred to as paradoxical vocal fold motion disorder. Patients with VCD usually present with intermittent shortness of breath of varying intensity, wheezing, stridor, choking, throat tightness, voice changes, or cough, and these symptoms often resolve quickly after relaxation or cessation of activity. Since first described as a distinct clinical entity in 1983, VCD remains underrecognized and the underlying cause(s) is not fully understood. Several studies suggest psychogenic or laryngeal hyperresponsiveness as possible underlying causes. Although VCD may have many causes, it can be a unique problem, especially in athletes because it often mimics and can be easily mistaken for exercise-induced bronchospasm, which may result in unnecessary medical treatment and delay in diagnosis. A detailed history, physical examination, and pulmonary function tests with flow-volume loops are important for excluding other diagnoses; however, the gold standard method for diagnosing VCD is by observation of the vocal cords with flexible laryngoscopy. The mainstay of treatment includes behavioral management guided by a speech-language pathologist, but optimal therapy often requires a multidisciplinary team involving a variety of specialties, including certified athletic training, pulmonology, otolaryngology, speech-language pathology, gastroenterology, allergy and immunology, and psychology, as appropriate. We reviewed the medical literature for VCD specifically in athletes, and this article discusses in detail the definition, epidemiology, possible pathophysiology, diagnosis, and treatment options.